Elaboramos historietas para informar cómo prevenir el contagio al coronavirus - Rosado Bacilio, Diana Paola (2021)
The purpose of this work of professional sufficiency is to promote significant learning referred to the session entitled: “We make cartoons to inform how to prevent the spread of the coronavirus”, developed in the area of communication for the third grade of Primary Education, taking into account The competence of: "writes various types of texts in their mother tongue", achieving the performance of planning, textualizing and reviewing when students write about the prevention measures caused by the coronavirus pandemic through a comic strip, adapting to the recipient and textual type of according to the communicative purpose, and incorporating a relevant vocabulary as well as some terms typical of the fields of knowledge. The production of texts through comics requires a capacity for organizing information, communicative purpose, creativity, originality to achieve the performance of the communication area. Therefore, the aim is for students to learn to communicate their experiences, anecdotes inside and outside of school. The learning session was evaluated through a text production card that verified the necessary criteria to specify the writing of the comic.